PREVALENSI AGE RELATED MACULAR DEGENERATION DI POLIKLINIK MATA BLU RSUP Prof. Dr. R. D. KANDOU MANADO PERIODE JANUARI 2013 – OKTOBER 2015 - Tany, Clarissa E.; Sumual, Vera; Saerang, J. S. M. (Universitas Sam Ratulangi, 2016)
Abstract: Age–related macular degeneration (AMD) is a visual impairment in central area of the retina (macula) that tends to be progressive. In developing countries, AMD becomes the most common cause of irreversible vision loss in people aged ≥50 years. This study aimed to obtain the prevalence of AMD in Department of Opthalmology at Prof. Dr. R. D. Kandou Hospital Manado from January 2013 to October 2015. This was a descriptive retrospective study using medical records of Department of Opthalmology. The results showed that there were 41 patients diagnosed as AMD. Based on sexes, AMD occured more frequent in male patients as many as 28 paients (68.3%). This disease was dominated by patients aged 61-70 years old as many as 16 patients (39%). There were 10 patients (24.4%) that had history of hypertension.Keywords: prevalence, AMD Abstrak: Age–related macular degeneration (AMD) adalah suatu gangguan penglihatan sentral retina (makula) yang bersifat progresif. Di negara berkembang AMD menjadi penyebab terbanyak hilangnya penglihatan yang ireversibel pada individu di atas 50 tahun. Penelitian ini bertujuan untuk mengetahui prevalensi AMD di Poliklinik Mata BLU RSUP Prof. Dr. R. D. Kandou Manado periode Januari 2013-Oktober 2015. Jenis penelitian ini deskriptif retrospektif dengan memanfaatkan data rekam medik di Poliklinik Mata BLU RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian memperlihatkan 41 pasien dengan diagnosis AMD. Berdasarkan jenis kelamin, AMD lebih banyak dialami oleh jenis kelamin laki-laki sebanyak 28 orang (68,3%), sedangkan untuk rentang umur didominasi oleh umur 61-70 tahun yaitu sebanyak 16 orang (39%). Terdapat 10 orang (24,4%) dengan riwayat hipertensi.Kata kunci: prevalensi, AMD